Hubungan Anemia dan Hipertensi pada Ibu dengan Kejadian Berat Badan Lahir Rendah (BBLR) di RSIA Husada Bunda Salo tahun 2022 - Amiroh, Fauziah; Lubis, Dumasari; Anggraini Dhilon, Dhini (Evidence Midwifery Journal, 2023)
Low Birth Weight (LBW) is a problem that often occurs in developing countries, especially countries with low socio-economic status. LBW is a condition where the baby born weighs <2500 grams, so it has a higher risk factor for morbidity and mortality. The aim of this research was to determine the relationship between anemia and hypertension in mothers and the incidence of LBW at RSIA Husada Bunda Salo in 2023. This type of research is Observational Analytical using a Retrospective Case Control research design. The population in this study is all data on newborn babies in 2022, totaling 1,040 babies. The sample in this study used a 1:1 ratio, namely 49 with case samples (babies who experienced LBW) and 49 with control samples (babies who did not experience LBW). The data collection tool in this research used a checklist sheet. Data analysis in this study used univariate and bivariate analysis. The research results showed that there was a relationship between maternal anemia and the incidence of LBW with a p value (0.004) and there was a relationship between hypertension in the mother and the incidence of LBW with a p value (0.001). It is hoped that health services, especially those at RSIA Husada Bunda Salo, can make efforts to provide information to village midwives about what LBW is and what factors can cause babies born to experience LBW